Measuring and Defining Children’s Fundamental Movement Skills - MAEVE MURRAY (2021)
Introduction: Fundamental movement skill (FMS) competence is associated with positive, health-related outcomes and can promote physical activity (PA) in adulthood. The revision of the Test of Gross Motor Development, Second Edition (TGMD-2) incorporated practitioner feedback reflecting societal changes, thus developing the Test of Gross Motor Development, Third Edition (TGMD-3). This study compared FMS proficiency according to TGMD-2 and TGMD-3. It further investigated the use of TGMD-3 in measuring FMS competence in older children. Methods: Two hundred and twelve children (n =112 boys; 52.8%; 12.5 ± 2.4 years) were recruited in South Wales. FMS skills were assessed using the TGMD-2 locomotor and object control and TGMD-3 locomotor and ball skills subscales. Inter- and intra-rater agreement was 92.7% and 90.3%, respectively. Mastery, near mastery (mastery/near mastery combined) and sex differences were subsequently investigated. To predict FMS performance against TGMD-2 total and subscale scores, regression analysis was undertaken using both these scores. Confirmatory factor analysis (CFA) was used to verify the factor structure of TGMD-3 and goodness-of-fit statistics were generated to understand how well the TGMD-3 assessment measures FMS ability in older children. Results: No child achieved mastery in either TGMD-2 or TGMD-3, while the proportion of children achieving mastery/near mastery (M/NM) decreased from TGMD-2 to TMGD-3 (skills measured in both assessments), reflecting notable differences in skill component criteria. Similar sex differences were observed in total assessment and subscale scores between the TGMD versions. There was a significant relationship between TGMD-2 and TGMD-3 total scores (ρ=0.945; p<0.01) and subsequent subscales: locomotor skills (ρ=0.922; p<0.01) and object control/ball skills (ρ=0.915; p<0.01). Overall TGMD-3 performance can be predicted from performance in both TGMD-2 subscales, with object control (TGMD-2) performance predicting ball skills proficiency (TGMD-3) and locomotor skill performance in TGMD-2 predicting TGMD-3 locomotor skill proficiency. A two-factor model was supported, however, the measure of best fit does not encompass all skills associated with TGMD-3 for older children. Conclusions: The findings support the removal of the underhand roll and demonstrates sex differences in TGMD-2 and TGMD-3 total mastery and object control/ball skills subscales. Skill component criteria changes suggest a higher degree of difficulty to achieve mastery in TGMD-3. The ability to predict TGMD-3 from TGMD-2 has important future implications, increasing inter-study comparability and thereby enabling significant advances in our understanding of FMS in youth. Identifying overall levels, trends and inequalities among children and young people is imperative to inform and deliver effective programmes and initiatives aimed at increasing PA, health-related fitness and physical competence levels.